Komparasi Tingkat Literasi Fisik Berdasarkan Kegiatan Ekstrakurikuler dan Jenis Kelamin - Muhammad Alif Andika; Lukmannul Haqim Lubay; Wulandari Putri; Achmad Syakur Fahri (Universitas Hamzanwadi, 2026)
This research was motivated by the importance of physical literacy as a foundation for lifelong active lifestyles, yet its implementation in Indonesia still faces various challenges, particularly in terms of conceptual understanding and measurement. This study aims to analyze differences in physical literacy levels based on extracurricular activities and gender among elementary school students in Cileunyi District, Bandung Regency. The research employed a quantitative approach with a causal-comparative design. A sample of 357 fifth-grade students was selected through proportional random sampling. The instrument used was the Physical Literacy Questionnaire for Children (PL-C Quest) which had been tested for validity and reliability in the Indonesian context. Data analysis used Mann-Whitney U and Kruskal-Wallis tests. The results showed no significant difference in physical literacy levels based on gender (p = 0.172), indicating equal learning opportunities between male and female students. In contrast, there was a significant difference based on the type of extracurricular activity (p < 0.001), where non-sports activities such as Coding, E-Sport, and Islamic activities showed higher scores in social and cognitive dimensions. This study concludes that extracurricular activities play a more dominant role in influencing physical literacy levels than gender. Schools are advised to optimize diverse and balanced extracurricular programs to support the holistic development of students' physical literacy.